Teachers' intrinsic vs. extrinsic instructional goals predict their classroom motivating styles. (April 2019) - Jang, Hye-Ryen
Abstract: We introduce the concept of teachers' intrinsic vs . extrinsic instructional goals and demonstrate its contribution to teachers' classroom motivating styles using independent samples across four studies. Based on self-determination theory, we hypothesized that the more teachers adopted intrinsic instructional goals the more they would rely on an autonomy-supportive motivating style, and the more they adopted extrinsic instructional goals the more they would rely on a controlling motivating style. Because no measure existed to assess intrinsic vs. extrinsic instructional goals, we created the new 4-scale, 16-item Teacher Goals Questionnaire (TGQ) in Study 1, using a pool of 72 candidate items and data from 212 fulltime K-12 teachers. In Study 2, we demonstrated the TGQ's construct and factorial validity by sampling 149 fulltime K-12 teachers. In Study 3, we tested our hypothesized model by sampling 147 fulltime K-12 teachers who reported their instructional goals on the TGQ and their motivating styles on two separate measures. Structural equation modeling analyses confirmed the hypothesized model. In Study 4, we replicated the findings from Study 3, using a multilevel sample (92 secondary teachers, 2749 students), a longitudinal research design, and student measures of teachers' motivating styles. The discussion focuses on instructional goals as key antecedents of teachers' classroom motivating styles. Highlights: I highlighted the new construct of teachers' instructional goals. Teachers' instructional goals were divided into intrinsic vs. extrinsic goals. Teachers' intrinsic goals predicted the autonomy supportive motivating style. Teachers' extrinsic goals predicted the controlling motivating style.